Traditional Edible Insects in the Monsang Tribe's Diet: Insights from Manipur, India - Somishon Keishing; Ng Maria Goretti; Th. Diana Devi; Chingriyo Raihing; Elmuonzo; Shishi Khawlneikim (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Edible insects have historically played a crucial role in providing food and nutrition for humans. Globally, thousands of insect species are consumed. The Monsang tribe, one of the Naga tribes primarily residing in Chandel district of Manipur, India, possess a distinctive culture and food preferences. This study aims to identify the variety of edible insects consumed by the Monsang tribe. Through purposive sampling, 150 subjects were selected for structured interviews to gather information. Thirteen species of edible insects were identified, including the carpenter worm (Cossus), wild bee hornet (Vespa mandarinia), and golden silk orb-weaver spider (Trichonephila clavipes), among others. The availability of these insects was found to be seasonal. Preparation methods varied and included roasting, steaming, and frying. The consumption of these insects was found to form a significant part of their diet, suggesting their potential as important ingredients for food and nutritional security.